Nature attacks! - Tarshis, Lauren (New York : Scholastic Press, 2015)
Tells the stories of four children who survived disasters, including a fourteen-year-old lone survivor of the shark attacks of 1916.
Includes bibliographical references (p. 148-152).
5.7
3-6
970L
Keywords: Animal attacks -- Juvenile literature; Disasters -- Juvenile literature; Survival -- Juvenile literature; Animal attacks; Disasters; Survival; Animal attacks; Disasters; Survival after airplane accidents, shipwrecks, etc; Animal attacks; Disasters; Survival